2018
DOI: 10.2967/jnumed.118.211466
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Ventilation–Perfusion Scan Is Associated with Pulmonary Hypertension in Sickle Cell Adults

Abstract: Pulmonary hypertension (PH) in adults with sickle cell disease (SCD) is associated with early mortality. Chronic thromboembolic pulmonary hypertension (CTEPH) is an important complication and contributor to PH in SCD, but likely underappreciated. Guidelines recommend ventilation-perfusion scintigraphy (V/Q) as imaging modality of choice to exclude CTEPH. Data on V/Q are limited in SCD. To compare the performance of V/Q with computed tomography pulmonary angiography (CTPA) and to report clinical outcomes associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…In our cohort, V/Q lung scintigraphy was frequently abnormal in this population as previously described [17], with a high frequency of mismatched segmental perfusion defects in SC patients. Similarly, a recent study observed that perfusion abnormalities on V/Q scintigraphy were associated with a higher proportion of PH [24]. In our present report, we have performed DSA in 18 patients, making it possible to identify two main patterns: patients with isolated poor subpleural perfusion and patients with lobar, segmental or subsegmental CTEPH lesions, as illustrated in figure 2.…”
Section: Discussionsupporting
confidence: 66%
“…In our cohort, V/Q lung scintigraphy was frequently abnormal in this population as previously described [17], with a high frequency of mismatched segmental perfusion defects in SC patients. Similarly, a recent study observed that perfusion abnormalities on V/Q scintigraphy were associated with a higher proportion of PH [24]. In our present report, we have performed DSA in 18 patients, making it possible to identify two main patterns: patients with isolated poor subpleural perfusion and patients with lobar, segmental or subsegmental CTEPH lesions, as illustrated in figure 2.…”
Section: Discussionsupporting
confidence: 66%
“…However, it is difficult to conclude (from the current data), whether PE is a cause or a consequence of ACS. 28 It is believed that patients with SCA are more prone to infection as a result of immune impairment because of asplenia. 29 Infection, by promoting an increase in inflammatory cytokines, can provoke thrombosis, especially in asplenic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic haemolysis may lead to depletion of nitric oxide (NO) and its precursors, thereby impairing vascular endothelial function [4][5][6]. A hypercoagulable state in SCD is promoted by several pathways, including NO depletion, platelet activation and functional asplenia, which could lead to in situ thrombosis [7][8][9]. A high cardiac output due to chronic anaemia may also induce endothelial dysfunction from flow-induced shear stress.…”
Section: Introductionmentioning
confidence: 99%